English language teaching in the Commonwealth Caribbean - Carrington, Lawrence D. (1970)
This article provides a brief overview of the problems encountered in the teaching and learning of English in the English-speaking Caribbean. It also identifies some of the linguistic research being undertaken on Caribbean dialects and languages
Keywords: Language education